Information on the Internet Regarding Orthognathic Surgery in Turkey: Is It an Adequate Guide for Potential Patients? - Nehir Canıgür Bavbek; Burcu Baloş Tuncer (Galenos Yayinevi, 2017)
Objective:To evaluate the quality of information on websites regarding orthognathic surgery in Turkey using the DISCERN toolkit.Methods:An Internet search was performed using the Google search engine with the terms "orthognathic surgery", "jaw surgery", "jaw operation", "correcting jaw surgery", and "surgery orthodontics." The first 25 websites obtained after searching for each term were evaluated. Duplicate websites, advertisements, discussion groups, links to research articles, videos, and images were not considered. The remaining websites were analyzed using the DISCERN toolkit. This toolkit is composed of 15 questions that were scored from 1 to 5. Results were calculated as mean scores, percentages, and ranges.Results:Among the 36 evaluated websites, 12 (33.3%) belonged to plastic surgeons, 11 (30.6%) belonged to orthodontists, 8 (22.2%) belonged to private dental clinics, 3 (8.3%) belonged to maxillofacial surgeons, 1 (2.8%) was a professional organization website, and 1 (2.8%) belonged to a private hospital. The Turkish Orthodontic Society had the only listed professional organization website. The mean total DISCERN score was 28/75 (range: 15-48). The overall quality of information in 44.4% of the websites was low. The main problems of websites were as follows: no mention of the aims, sources, and production time of information; no links for additional sources of information; and no information for patient carers.Conclusion:The quality of web-based information on orthognathic surgery was generally low. Higher quality information provided by public organizations that do not have profit concerns is required.